High temperature internal friction in Ni50.3Ti29.7Zr20 shape memory alloy. (June 2019) - Zuo, Shungui; Wu, Riming; Pang, Guobo; Yang, Yanping; Jin, Mingjiang
Abstract: The internal friction at temperature up to 980 K in Ni50.3 Ti29.7 Zr20 (at.%) high temperature shape memory alloy was investigated. A relaxation peak was observed at about 750 K for 0.1 Hz. Its activation parameters were determined, H act = 1.82 ± 0.04 eV, τ 0 = 2.22 × 10 −12 s. Similar relaxation peak with the activation enthalpy of about H act = 1.42 eV was observed in NiTi binary alloy at a slightly lower temperature. Alloying of Zr is found to increase the activation enthalpy of this relaxation. The mechanism of this relaxation was discussed based on a Zener relaxation related to the short-range diffusion of Ni. Graphical abstract: Image 1 Highlights: A relaxation peak at approximately 750 K for 0.1 Hz is observed in Ni50.3 Ti29.7 Zr20 alloy. The activation parameters of the peak is determined as H act = 1.82 ± 0.04 eV, τ 0 = 2.22 × 10 −12 s. Similar relaxation peak was observed in NiTi binary alloy. Alloying of Zr increased the activation enthalpy of the relaxation.